Barbatic acid from Cladia aggregata (lichen): Cytotoxicity and in vitro schistosomicidal evaluation and ultrastructural analysis against adult worms of Schistosoma mansoni. (June 2020) - Silva, H.A.M.F.; Aires, A.L.; Soares, C.L.R.; Sá, J.L.F.; Martins, M.C.B.; Albuquerque, M.C.P.A.; Silva, T.G.; Brayner, F.A.; Alves, L.C.; Melo, A.M.M.A.; Silva, N.H.
Abstract: Schistosomiasis is one of the most significant neglected tropical diseases, affecting around 260 million people worldwide, and Praziquantel is currently the only available drug for the treatment of infected persons. Thus, the search for new schistosomicidal compounds is urgent. The objective of this study was to investigate of the schistosomicidal effect of barbatic acid, a lichen metabolite, on adult worms of Schistosoma mansoni . The in vitro schistosomicidal effect was evaluated through the assessment of motility and mortality, cellular viability of the worms and ultrastructural analysis through scanning electron microscopy. To evaluate the cytotoxicity of barbatic acid, a cell viability assay was performed with human peripheral blood mononuclear cells . Barbatic acid showed a schistosomicidal effect after 3 h of exposure. At the end of 24 h the concentrations of 50–200 μM presented lethality on the worms. Motility changes were observed at sublethal concentrations. The IC50 obtained by the cell viability assay for S. mansoni was 99.43 μM. Extensive damage to the worm's tegument was observed from 25 μM. No cytotoxicity was observed on human peripheral blood mononuclear cells. This report provides data showing the schistosomicidal effect of barbatic acid on S. mansoni, causing death, motility changes and ultrastructural damage to worms. In addition, barbatic acid was shown to be non-toxic to human peripheral blood mononuclear cells at concentrations that are effective against S. mansoni . Graphical abstract: Unlabelled Image Highlights: Barbatic acid exhibited schistosomicidal effect against adult S. mansoni . Motility changes were observed in S.mansoni at all concentrations after 24 h. Tegumentary damages were caused by the barbatic acid in Schistosoma mansoni . No cytotoxicity was observed on PBMC exposed to barbatic acid after 72 h.